Metaverse Optimization: Exploration of the Potential of Ecotourism in Geopark Merangin Jambi Based on Virtual Reality - Andriana, Septiana Dewi; Rismayanti (Yayasan Cita Cendekiawan Al Khwarizmi, 2024)
Merangin Jambi Geopark is a world heritage site that has been recognized by UNESCO. The attractions of the Merangin Geopark are very diverse, ranging from lakes, caves, waterfalls, hot springs, traditional forests, to ancient tree fossils that are older than the island of Sumatra (the Permian Araucarioxylon fossil is 300 million years old). Unfortunately, not many people know the beauty behind this earth park, even the Merangin Geopark is in a state of